2017
DOI: 10.1111/twec.12593
|View full text |Cite
|
Sign up to set email alerts
|

External adjustment in oil exporters: The role of fiscal policy and the exchange rate

Abstract: After the decline in oil prices, many oil exporters face the need to improve their external balances. Special characteristics of oil exporters make the exchange rate an ineffective instrument for this purpose and give fiscal policy a sizeable role. These conclusions are supported by regression analysis of the determinants of the current account balance and of the trade balance. The results show little or no relationship with the exchange rate and, especially for the less diversified oil exporters, a strong rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(64 reference statements)
0
7
0
3
Order By: Relevance
“…The fiscal policies of these countries are pro-cyclical, and therefore, when the oil price and, thus, oil revenues are high, then there is a fiscal expansion, which results in higher domestic price levels (Sturm et al 2009, among others). Hasanov (2013) for Azerbaijan and Behar and Fouejieu (2016) for the panel of oil exporters, including Russia, Kazakhstan and Azerbaijan, show again the dominant position of fiscal policy and the importance of government spending in the macroeconomic functioning. The Asian Development Bank report discusses tremendous government spending in Azerbaijan especially when oil price was higher (Asian Development Bank 2014).…”
Section: Empirical Estimations and Discussionmentioning
confidence: 99%
“…The fiscal policies of these countries are pro-cyclical, and therefore, when the oil price and, thus, oil revenues are high, then there is a fiscal expansion, which results in higher domestic price levels (Sturm et al 2009, among others). Hasanov (2013) for Azerbaijan and Behar and Fouejieu (2016) for the panel of oil exporters, including Russia, Kazakhstan and Azerbaijan, show again the dominant position of fiscal policy and the importance of government spending in the macroeconomic functioning. The Asian Development Bank report discusses tremendous government spending in Azerbaijan especially when oil price was higher (Asian Development Bank 2014).…”
Section: Empirical Estimations and Discussionmentioning
confidence: 99%
“…For instance, the External Balance Assessment (EBA)-lite, which the IMF (2016) developed, uses an export volume elasticity of -0.71 (and an import volume elasticity of 0.92). For oil-exporting countries, the price elasticity is much smaller, close to zero, because oil exports are priced in U.S. dollars (Behar and Fouejieu 2016). Using cointegration methods without including an exchange rate variable, Aba, Aipi and Irau (2012abc) studied the price elasticity of coffee, cocoa, and palm oil exports in PNG, and found that results are not statistically significant.…”
mentioning
confidence: 99%
“…Podobnie, (z kilkoma wyj tkami), producenci ropy s cenobiorcami, wi c ca kowite zyski z eksportu mog nie by istotne. (Behar, 2016).…”
Section: Implikacje Spadku Cen Dla Krajowych Polityk Makroekonomicznychunclassified
“…Ponadto, wysoka zale no od importu oraz ograniczone mo liwo ci substytucji, ograniczaj odpowied wolumenów importu na ruchy cen relatywnych. (Behar, 2016).…”
Section: Implikacje Spadku Cen Dla Krajowych Polityk Makroekonomicznychunclassified
See 1 more Smart Citation